The Reinforcing Effect of Sugar Palm Fiber on PP - Kenneth Genesius Han; Juliana Anggono; Peter Jonathan (Institute of Research and Community Outreach - Petra Christian University, 2021)
Natural fibers have the ability to reinforce polymeric materials. In this work, sugar palm fibers were added as a reinforcement agent to a polypropylene (PP) matrix to form biocomposites. Flexural strength measurement in accordance with ASTM D790-17 was carried out on PP composites with the sugar palm fiber content changed from 0 to 30 wt.% in 5 wt.% steps. The flexural strength data show a composition dependence on the fiber content with a maxima (52.09 MPa) obtained in 15 wt.% fibers. Sugarcane bagasse-PP composite together with wood board composite and neat PP as existing materials by automotive industry were used as reference material in the study. This sugar palm fiber-PP composites offer lower density in comparison with wood board composites and PP. The area density of the composites is in the range of 1285-1635 g/m2 for the composition studied while PP and wood board have area density of 1466 and 1700 g/m2 respectively.